Purinergic Receptor Antagonists: A Complementary Treatment for Hypertension - Rocio Bautista-Pérez; Martha Franco (MDPI AG, 2024)
The treatment of hypertension has improved in the last century; attention has been directed to restoring several altered pathophysiological mechanisms. However, regardless of the current treatments, it is difficult to control blood pressure. Uncontrolled hypertension is responsible for several cardiovascular complications, such as chronic renal failure, which is frequently observed in hypertensive patients. Therefore, new approaches that may improve the control of arterial blood pressure should be considered to prevent serious cardiovascular disorders. The contribution of purinergic receptors has been acknowledged in the pathophysiology of hypertension; this review describes the participation of these receptors in the alteration of kidney function in hypertension. Elevated interstitial ATP concentrations are essential for the activation of renal purinergic receptors; this becomes a fundamental pathway that leads to the development and maintenance of hypertension. High ATP levels modify essential mechanisms implicated in the long-term control of blood pressure, such as pressure natriuresis, the autoregulation of the glomerular filtration rate and renal blood flow, and tubuloglomerular feedback responses. Any alteration in these mechanisms decreases sodium excretion. ATP stimulates the release of vasoactive substances, causes renal function to decline, and induces tubulointerstitial damage. At the same time, a deleterious interaction involving angiotensin II and purinergic receptors leads to the deterioration of renal function.